2019
DOI: 10.1080/15548627.2019.1591672
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy regulates mitochondrial network signaling, oxidative stress, and apoptosis during myoblast differentiation

Abstract: Macroautophagy/autophagy is a degradative process essential for various cellular processes. We previously demonstrated that autophagy-deficiency causes myoblast apoptosis and impairs myotube formation. In this study, we continued this work with particular emphasis on mitochondrial remodelling and stress/ apoptotic signaling. We found increased (p < 0.05) autophagic (e.g., altered LC3B levels, increased ATG7, decreased SQSTM1) and mitophagic (e.g., BNIP3 upregulation, mitochondrial localized GFP-LC3 puncta, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
125
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(134 citation statements)
references
References 50 publications
6
125
1
2
Order By: Relevance
“…As a selective form of autophagy, mitophagy is a major pathway involved in the clearance of dysfunctional or damaged mitochondria 20,21 . LC3II is a hallmark protein associated with autophagosome formation 42 .…”
Section: Discussionmentioning
confidence: 99%
“…As a selective form of autophagy, mitophagy is a major pathway involved in the clearance of dysfunctional or damaged mitochondria 20,21 . LC3II is a hallmark protein associated with autophagosome formation 42 .…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to determine whether any of the previously identified roles for the ERK5 pathway in development, physiology, or disease represent an underlying role for mitochondrial degradation. For example, ERK5 signaling is well established to play an anti-apoptotic role, and mitochondria harbor several proapoptotic molecules including cytochrome c, Smac/DIABLO, and AIF (Adrain, Creagh, & Martin, 2001;Baechler, Bloemberg, & Quadrilatero, 2019;Nithianandarajah-Jones et al, 2012). It is possible that active ERK5 signaling antagonizes autophagy in part through elimination of pro-apoptotic molecules via delivery of mitochondria to lysosomes for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas activation levels of ERK1/2 and mTOR do not appear to be modified ( Figure 2E), we observed that FOXO3 level, which has been demonstrated to impair muscle progenitors proliferation (31,32), is significantly decreased in CCL-136 Low (Figure 2E). During myogenesis, it was shown that the caspases, and notably caspase-3, activation is required at a 'sub-apoptotic' level to engage myoblasts in differentiation (33)(34)(35). Caspases are cysteine proteases executioners of apoptosis.…”
Section: Loss Of Ant1 Confers Selective Advantage To Tumor Cells By Mmentioning
confidence: 99%